2016
DOI: 10.1051/matecconf/20166701006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2D Hexagonal Mesoporous Silica Using Amino Acid-based Surfactant Templating

Abstract: Abstract. Ordered 2D hexagonal and parallel arranged pore channel mesoporous silica materials with homogeneous size and spherical shape have been synthesized by using amino acid-based surfactant templating, their ordered mesostructures were characterized by infrared spectroscopy, X-ray diffraction patterns (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and nitrogen sorption analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Subsequently, the surface pore structure of the KIT-6 mesoporous molecular sieve was investigated by using Brunauer-Emmett-Teller (BET) nitrogen adsorption-desorption isotherms, and a typical type IV adsorption isotherm with a sharp capillary coalescence step and a H1-type hysteresis loop appeared under higher relative pressures. [31][32][33] Monolayer adsorption and multilayer adsorption were observed sequentially as the relative pressure increased. The adsorption isotherm steepened when capillary condensation occurred under pressure, and surface adsorption eventually occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the surface pore structure of the KIT-6 mesoporous molecular sieve was investigated by using Brunauer-Emmett-Teller (BET) nitrogen adsorption-desorption isotherms, and a typical type IV adsorption isotherm with a sharp capillary coalescence step and a H1-type hysteresis loop appeared under higher relative pressures. [31][32][33] Monolayer adsorption and multilayer adsorption were observed sequentially as the relative pressure increased. The adsorption isotherm steepened when capillary condensation occurred under pressure, and surface adsorption eventually occurred.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the surface pore structure of CsPbBr 3 / SBA-15 composites, Brunauer−Emmett−Teller (BET) nitrogen adsorption-desorption isotherm was studied and revealed a typical type IV adsorption isotherm with sharp capillary condensation step and H1-type hysteresis loop at a higher relative pressure. [37,38] With increasing relative pressure, monolayer adsorption and multilayer adsorption occur successively. When capillary condensation can occur under pressure, the adsorption isotherms become steeper, and finally the surface adsorption is observed.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (22) reported fabrication of mesoporous silicas at room temperature by using tailor-made polymers (C 16 -L-His, C 16 -L-Pro, and C 16 -L-Trp) as SDA, which are derived from amino acids with ring structures. Xu et al (23) reported the synthesis of ordered 2D hexagonal and parallel pore channel mesoporous silica materials with homogeneous size and spherical shape by using amino acid surfactant templating. Zhang et al (24) used amino acids to introduce hierarchical mesoporosity into a microporous zeolite having the LTA topology.…”
Section: Porous Functional Silica Structures and Their Synthesismentioning
confidence: 99%